2010
DOI: 10.1002/adfm.200901632
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Bonding Assembly of Multifunctional Oxide Nanocomposites

Abstract: The synthesis, functionalization and assembly of metal oxide nanoparticles BaTiO3 and CoFe2O4 is presented. The ferroelectric (BaTiO3) and ferromagnetic (CoFe2O4) oxide nanoparticle surfaces are directly functionalized via the anchoring of phosphonic acid and aminosilane molecules that engender the nanoparticles with terminal carboxylic acid and amine functional groups, respectively. These promote the electrostatic self-assembly of the particles in non-polar solvents and permit the synthesis of more chemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The synthesis of the magnetostrictive nanoparticles used in polymer‐based ME particulate nanocomposites is well discussed in the literature 52–57. On the other hand, the interface effects between nanoparticles and the polymer matrix has received only little attention.…”
Section: Polymer‐based Magnetoelectric Materialsmentioning
confidence: 99%
“…The synthesis of the magnetostrictive nanoparticles used in polymer‐based ME particulate nanocomposites is well discussed in the literature 52–57. On the other hand, the interface effects between nanoparticles and the polymer matrix has received only little attention.…”
Section: Polymer‐based Magnetoelectric Materialsmentioning
confidence: 99%
“…Tailored fabrication of novel ceramic materials composed of periodic arrays of micro‐ and nanoscale phases is still in its infancy. For example, it has been shown that chemical functionalization and bonding can be used to predictably assemble distinctly different sets of oxide nanoparticles . Approaches such as these can offer general fabrication platforms to produce dense hybrid composites with property combinations of interest in a broad range of applications including energy storage, photon harvesting, and catalysis.…”
Section: Grand Challenges For Ceramic Sciencementioning
confidence: 99%
“…The structural parameters play a crucial role in determining and optimizing the sensor-related properties (Calfen and Mann 2003;Tretyakov 2003;Rawle 2007;Perry and Carter 2006;Evans et al 2010;Colfen and Antonietti 2005;Demortière et al 2008;Shevchenko et al 2006;Koziej et al 2014;Ansari et al 2014). In order to achieve desired shape and size with enhanced functional properties, bottom-to-top wet chemical approach was undertaken to synthesize functional nanopowder for their chemical and biological studies.…”
Section: Methodsmentioning
confidence: 99%